Vascularised and Non-Vascularised Adipofascial Flap Applications in Tissue Trauma with Tendon Injury, Flap Viability and Tendon Healing a Hystological and Scintigraphical Rat Model Study - Mehmet Yucens; Ahmet Nadir Aydemir; Tarık Sengoz; Gulcin Abban Mete; Nusret Ök; Mehmet Rauf Koç; Ahmet Fahir Demirkan (Medicina)
Background and Objectives: Complex wounds in the hand and distal lower extremities pose challenges in reconstructive surgery, often involving critical structures like tendons. Tendon injuries, prevalent in such wounds, necessitate optimal repair methods for functional recovery. This study investigates the impact of vascularised and nonvascularised adipofascial tissue on tendon repair, focusing on early healing stages, mobilisation, and scintigraphic evaluation of flap vascularity. Materials and Methods: Wistar Albino rats were divided into groups undergoing primary tendon repair, vascularised adipofascial flap application, or nonvascularised flap application. Scintigraphic evaluation and histopathological assessment were performed to analyse healing processes. Results: Pedicle-free flaps support healing in tendon injuries without negatively affecting medium-term outcomes. Vascularised flaps exhibit faster healing. The scintigraphic analysis showed that the static measurements of the late phase were statistically significantly higher in the group with the non-vascularised adipofascial flap (p = 0.038). The mean perfusion reserve was higher in the vascularised pedicled adipofascial flap group than the non-vascularised adipofascial flap group. Scintigraphic analysis highlights the viability of pedicle-free flaps. Conclusions: Pedicle-free adipofascial flaps support the healing of the tendon without complicating the results, while vascularised flaps show accelerated healing. These findings provide valuable insights into optimising tendon repair strategies using adipofascial flaps, with implications for enhancing functional recovery in complex wounds.